Cardiac Fibro-Adipocyte Progenitors Express Desmosome Proteins and Preferentially Differentiate to Adipocytes Upon Deletion of the Desmoplakin Gene. Issue 1 (24th June 2016) - Lombardi, Raffaella; Chen, Suet Nee; Ruggiero, Alessandra; Gurha, Priyatansh; Czernuszewicz, Grazyna Z.; Willerson, James T.; Marian, Ali J.
Abstract : Rationale: : Mutations in desmosome proteins cause arrhythmogenic cardiomyopathy (AC), a disease characterized by excess myocardial fibroadipocytes. Cellular origin(s) of fibroadipocytes in AC is unknown. Objective: : To identify the cellular origin of adipocytes in AC. Methods and Results: : Human and mouse cardiac cells were depleted from myocytes and flow sorted to isolate cells expressing platelet-derived growth factor receptor-α and exclude those expressing other lineage and fibroblast markers (CD32, CD11B, CD45, Lys76, Ly −6c and Ly 6c, thymocyte differentiation antigen 1, and discoidin domain receptor 2). The PDGFRA pos :Lin neg :THY1 neg :DDR2 neg cells were bipotential as the majority expressed collagen 1 α-1, a fibroblast marker, and a subset CCAAT/enhancer-binding protein α, a major adipogenic transcription factor, and therefore, they were referred to as fibroadipocyte progenitors (FAPs). FAPs expressed desmosome proteins, including desmoplakin, predominantly in the adipogenic but not fibrogenic subsets. Conditional heterozygous deletion of Dsp in mice using Pdgfra-Cre deleter led to increased fibroadipogenesis in the heart and mild cardiac dysfunction. Genetic fate mapping tagged 41.4±4.1% of the cardiac adipocytes in the Pdgfra-Cre : Eyfp:Dsp W /F mice, indicating an origin from FAPs. FAPs isolated from the Pdgfra-Cre : Eyfp:Dsp W /F mouse hearts showed enhanced differentiation to adipocytes. Mechanistically, deletion of Dsp was associated with suppressed canonical Wnt signaling and enhanced adipogenesis. In contrast, activation of the canonical Wnt signaling rescued adipogenesis in a dose-dependent manner. Conclusions: : A subset of cardiac FAPs, identified by the PDGFRA pos :Lin neg :THY1 neg :DDR2 neg signature, expresses desmosome proteins and differentiates to adipocytes in AC through a Wnt-dependent mechanism. The findings expand the cellular spectrum of AC, commonly recognized as a disease of cardiac myocytes, to include nonmyocyte cells in the heart. Abstract : Supplemental Digital Content is available in the text.